2003
DOI: 10.1097/00005110-200305000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Values and a Changing Nurse Workforce

Abstract: Management strategies to meet nurses' values and increase their satisfaction and retention are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 29 publications
11
79
0
3
Order By: Relevance
“…The finding that older generations had greater years of experience, but less educational preparation than younger generations is consistent with previously published studies [14,42] . In this sample, the percentage of BSN-prepared nurses increased with each preceding generation reflecting current national educational trends among nurses.…”
Section: Resultssupporting
confidence: 92%
“…The finding that older generations had greater years of experience, but less educational preparation than younger generations is consistent with previously published studies [14,42] . In this sample, the percentage of BSN-prepared nurses increased with each preceding generation reflecting current national educational trends among nurses.…”
Section: Resultssupporting
confidence: 92%
“…Prior research has consistently demonstrated that organizational commitment is positively associated with organizational effectiveness and performance (McNeese-Smith & Crook, 2003;Testa, 2001) and negatively related to turnover. Manlove and Guzell (1997) found that organizational commitment had a greater influence on turnover than did job satisfaction.…”
Section: The Influence Of Organizational Commitment On Organizationalmentioning
confidence: 99%
“…[14,15] Profesyonel değerler yaş, cinsiyet, medeni durum ve eğitim durumu gibi sosyo-demografik faktörlerden etkilenebilmektedir. [14,[16][17][18] Ayrıca literatürde mesleki kıdemin, uzmanlık alanının ve pozisyonun da hemşirelerin profesyonel değerlerini etkilediği belirtilmiştir. [14] Hemşirelik mesleği için çok önemli bir kavram olan profesyonel değerlerin ve etkileyen faktörlerin belirlenmesi, bu konuya gerek mesleki gerekse hizmet içi eğitimlerde yer verilmesi önem taşımaktadır.…”
Section: Introductionunclassified